1995
DOI: 10.1007/bf00176441
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and structural analysis of the rat RT1.E u and RT1.Aw3 l genes, and of genes related to RT1.O and RT1.C

Abstract: A cDNA library was constructed using mRNA isolated from the R21 strain of rats which have the major histocompatibility complex (MHC) haplotype RT1.AlBlDlEu and the growth and reproduction complex (grc) genotype grc+. The cDNA clones that hybridized with the class I probes pAG64c and pARI.5 and were 1.3-1.7 kilobases were selected. Full-length clones were identified by sequencing partially the 5' and 3' ends of each clone, by the presence of a start codon at the 5' end, and by a polyadenylation sequence at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Several class I fragments have been partially sequenced. By comparison with published data, the class I exon 2 sequence of BamHI fragment 1 is nearly identical with the RT1-C c clone cc1 (23), and fragment 4 was identified as the RT1-E gene (24,25). Exon 2 sequences of fragments 2, 19, 23, and 10 revealed highest similarity (above 90%) to class Ia genes of the RT1-A region, but not to H2-D or H2-Q genes, which reside in the corresponding part of the mouse MHC.…”
Section: Class I Genesmentioning
confidence: 86%
See 1 more Smart Citation
“…Several class I fragments have been partially sequenced. By comparison with published data, the class I exon 2 sequence of BamHI fragment 1 is nearly identical with the RT1-C c clone cc1 (23), and fragment 4 was identified as the RT1-E gene (24,25). Exon 2 sequences of fragments 2, 19, 23, and 10 revealed highest similarity (above 90%) to class Ia genes of the RT1-A region, but not to H2-D or H2-Q genes, which reside in the corresponding part of the mouse MHC.…”
Section: Class I Genesmentioning
confidence: 86%
“…It is unknown at present how many of the class I genes are indeed expressed. Among the class I genes described in the RT1-C/E/M region before, RT1-E (24,25), RT-BM1 (26,27,29), RT1-N1 (30), RT1-M3 (32), and RT1-M4 (21) have been fine mapped now, and for some of them restricted tissue distribution could be shown (Table II). Genes of the first class I cluster, such as RT1-E, as well as class I sequences obtained from this region, are more similar to rat class Ia genes than to other rat class I genes or mouse H2-D, Q, T, M genes.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the prototype gene to the class I RT1-T24 gene family was originally identified as a pseudogene in the haplotype r21 (Salgar et al 1995). In RT1 n , all four RT1-T24 genes are presumably functional, based on their coding potential.…”
Section: Genome Research 635mentioning
confidence: 99%
“…In the latter case, it has been clearly shown that the MAPRTLLL or MAPRTLLLL peptides resulting were unable to bind significantly to H2-Qa1 [63], and translation of those class I molecules would therefore not result in the inhibition of NK cells via their CD94/NKG2A receptors. Whilst all rat class Ia sequences where this sequence is known to start with the first methionine, this first ATG is not present in many rat class Ib molecules including RT1-C l [30] and RT1-E u [25], and the second methionine is therefore used. Since both RT1-C l and RT1-E u have been shown to be potential activators of allorecognition by NK cells [62,64], there is therefore a correlation whereby the molecules that can inhibit NK cell activity also have a functional codon for the first methionine, and the ones that can be recognised by NK activatory receptors do not.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we have found that transcripts for molecules very closely related to those identified in placenta can also be found in neurospheres [23], which are in vitro cultures of neural stem cells [24], as well as in cDNA libraries of lymphoid tissues. Altogether, these form a group of sequences that are very closely related to one another, and more distantly to the RT1-E u molecule [25]. We have therefore chosen to name the members of this group RT1-E2, and report here on their characterisation.…”
Section: Introductionmentioning
confidence: 99%